Live yeast supplementation improves apparent nutrient digestibility of high-fibre diet in mature quarter horses - Silvia Sandrini; Vera Perricone; Alessia Pea; Clara Cenati; Giovanni Savoini; Gianluca Baldi; Alessandro Agazzi (Italian Journal of Animal Science, 2025)
This study aimed to evaluate the effects of live yeast (Saccharomyces cerevisiae, BioCell® S12, DBVPG 48 SF, Mazzoleni spa, Bergamo, Italy) in mature horses fed a high forage:concentrate ratio diet on apparent nutrients digestibility. Eight American Quarter Horse (475.5 kg; 8.5 years) were supplemented with S. cerevisiae (3 g/horse/d; LY) or not (CTR) in a two-periods crossover design of 28 days each, with a 7-days adaptation period, and a confinement in the last 5 days. Body weight (BW) was measured at 0, 15, 23 and 28 days for each period, and dry matter intake (DMI) determined during confinement. Individual faecal samples were collected for five consecutive days at the end of each period (23-28d). Data were analysed using a MIXED procedure for repeated measurements of SAS. No effects of S. cerevisiae supplementation were observed on BW and DMI during the whole trial. Yeast improved apparent nutrient digestibility of dry matter (58.22% vs. 53.95%; ±1.38; p < 0.05), organic matter (59.86% vs. 55.35%, ±1.38; p = 0.04), crude protein (59.71% vs. 55.09%, ±1.44; p = 0.04), neutral detergent fibre (52.53 vs. 46.65%, ±1.78; p = 0.04), acid detergent fibre (47.96% vs. 41.02%, ±2.03; p = 0.03), and cellulose (59.43% vs. 53.56%, ±1.75; p = 0.04), with a positive trend on hemicellulose (57.61% vs. 52.86%, ±1.59; p = 0.06). No significant effects were observed on apparent digestibility of crude fat, non-structural carbohydrates and digestible energy. In the present study, the administration of S. cerevisiae to mature Quarter horses on high forage:concentrate diet significantly improved the apparent nutrient digestibility, with especial remark to fibrous fractions of the diet.